Redox‐Controlled Olefin (Co)Polymerization Catalyzed by Ferrocene‐Bridged Phosphine‐Sulfonate Palladium Complexes. Issue 51 (2nd November 2015) - Chen, Min; Yang, Bangpei; Chen, Changle
Abstract: The facile and reversible interconversion between neutral and oxidized forms of palladium complexes containing ferrocene‐bridged phosphine sulfonate ligands was demonstrated. The activity of these palladium complexes could be controlled using redox reagents during ethylene homopolymerization, ethylene/methyl acrylate copolymerization, and norbornene oligomerization. Specifically in norbornene oligomerization, the neutral complexes were not active at all whereas the oxidized counterparts showed appreciable activity. In situ switching between the neutral and oxidized forms resulted in an interesting "off" and "on" behavior in norbornene oligomerization. This work provides a new strategy to control the olefin polymerization process. Abstract : From one to another : Interconversion between the neutral and oxidized forms of a series of Pd complexes with ferrocene‐bridged phosphine sulfonate ligands was demonstrated. The neutral and oxidized Pd catalysts had dramatically different activities in ethylene polymerization, ethylene/methyl acrylate (E–MA) copolymerization, and norbornene (NB) oligomerization.